Perancangan Sistem Informasi Siswa Berbasis Website di Perguruan Darulfunun El-Abbasiyah - Siswati Siswati; Yelsi Oktavia; Fatma Sari; Mona Eliza; Afifi Fauzi Abbas; Abdullah A Afifi (Journal of Regional Development and Technology Initiatives, 2023)
The process of managing student data which is still manual makes the governance of educational institutions less than optimal. Often invalid input data and unsynchronized data are caused by the unavailability of a good system for managing it. This makes management unable to create transparency in internal processes, so it will take a lot of time and energy. This article is a technical report on the implementation of the website-based student information system design process. This implementation was carried out at Darulfunun El-Abbasiyah College from January 2019 to July 2023. This implementation process involved many stages of development and improved versions. This system is also tested directly in management and receives input to be improved and then tested again. The development of the student information system helps supervision, avoiding misuse and inaccuracy of information. This student information system also reduces misunderstandings with parents, guardians, religious ministries and education offices due to data that is inaccurate or cannot be presented within a certain time.